KORELASI ANTARA KECERDASAN INTERPERSONAL DENGAN HASIL BELAJAR IPS SISWA KELAS V DI SD GUGUS IV ABIANSEMAL TAHUN PELAJARAN2017/2018 - Dewa Saputra (Universitas Pendidikan Ganesha, 2018)
The research was aimed at determining the significant correlation between the interpersonal intelligence and the social science learning achievement of the fifth-grade students in Elementary School of Gugus IV Abiansemal in the academic year 2017/2018. The type of this research was ex-post facto using asymmetric correlation.The population of this research was the fifth-grade students of Elementary School Gugus IV Abiansemal in the academic year 2017/2018 which consisted of 145 students. The sample was decided by the proportional random sampling technique in which the significance level was 5% and 106 students were obtained from the population. The data collection was conducted through the documentation of students’ learning achievement in social science and the questionnaire about the students’ interpersonal intelligence. The prerequisite test used the normality test of data distribution. After conducting prerequisite test, the hypothesis test using correlation analysis Product Moment was carried out. Based on the analysis result, it was obtained that = 0,484. In the significance level of 5% in which n = 106, it was obtained that = 0,195. As > = 0,484 > 0,195, it can be mentioned that stating that there is no significant correlation between the interpersonal intelligence and the social science learning achievement in the fifth-grade in Elementary School Gugus IV Abiansemal in the academic year 2017/2018 was rejected and was accepted. It can be concluded that there is a significant correlation between the interpersonal intelligence and the social science learning achievement of the fifth-grade students in Elementary School Gugus IV Abiansemal in the academic year 2017/2018. For the result obtained the positive scatterplot of positive correlation, it can be stated that the higher interpersonal intelligence that the students have, the higher social science learning achievement that they will obtain